The Ionospheric Total Electron Content Behavior at Equatorial and Polar Stations - Hamzah, S. Z.; Homam, M. J. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The characteristic of ionosphere behavior is of spatial and temporal variations. The ionosphere behavior was determined by identifying the total electron content (TEC) variation. The investigation on TEC variation had been made over an equatorial station, Libreville (NKLG) station (0.4162° N, 9.4673° E), and a polar station, Ny-Alesund (NYA1) station (78.9235° N, 11.9099° E) in year 2009 and 2013, each representing different level of solar activity. The hourly averaged vertical TEC (VTEC) is used to observe the TEC variation under diurnal, seasonal, and geomagnetic storm variations. The diurnal TEC variations in March and September 2009 experienced a double TEC peak structure. The TEC variation over the NKLG station in the low and high solar activity depicted the same observation where the TEC variation began to rise until it reached its maximum TEC peak around noon to the late evening, and it falls after the sunset hours until it reached its minimum TEC at pre-dawn hours. The diurnal TEC variations for all months at the NYA1 station showed rapid fluctuations of TEC by the presence of more peaks of TEC. The seasonal TEC variations showed its highest TEC peak in spring and lowest TEC peak in summer at NKLG station during both 2009 and 2013. The great fluctuations of TEC obviously observed during the winter and spring. The maximum seasonal TEC peak at NYA1 station mainly occurred around the late evening hours to the extent of pre-dawn hours. The moderate geomagnetic storm on 22 July 2009 caused an increment of TEC at both stations during the storm time meanwhile the moderate geomagnetic storm on 6 July 2013 caused a decrement of TEC at both stations during the storm time.